Multidimensional Sources of Political Legitimacy Among Kyai in Tapal Kuda Area - Akmal Mundiri; Firda Fina Fitriya; Hasan Jali (AL-TAHRIR, 2026)
This study aims to analyze and map the multidimensional sources of political legitimacy among Kyai (Islamic clerics) in Indonesia by employing a qualitative approach and a case study method. Data were collected through in-depth interviews with Kyai directly involved in political contests, as well as through observation of their socio-political activities. The findings reveal that the political legitimacy of Kyai is not singular but is constructed through the interaction of four main dimensions: (1) religious and moral legitimacy, (2) institutional legitimacy derived from pesantren ownership, (3) legitimacy obtained through political and economic networks, and (4) communicative legitimacy in the digital sphere. The first two dimensions align with Max Weber’s theory of legitimacy, charismatic, and traditional types while the latter two represent new forms of legitimacy that are not accommodated within the Weberian framework. Based on these findings, this study formulates a new theoretical model called the Adaptive Political Legitimacy of Kyai Theory, which integrates classical legitimacy with instrumental and communicative dimensions. This theory explains that the political legitimacy of Kyai in Indonesia is adaptive to social, economic, and technological changes, positioning Kyai not only as spiritual leaders but also as strategic actors in shaping the political consciousness of the Muslim community. This study contributes theoretically to the development of the concept of political legitimacy within the context of Indonesian Islam and provides practical insights for understanding the evolving role of Kyai in the increasingly complex and digitally connected modern era.